A dialectical-relational approach to anti-trans sentiments on Hupu. (December 2022) - Peng, Altman Yuzhu; Sun, Yu
Highlights: Biological commentary or anti-foreign-nation political commentary significantly increase user engagement on Hupu. Anti-trans posts involving a humorous tone showcase many male Hupu users' distorted dissent against trans-inclusivity. Biological commentary reveals the perpetuation of sex essentialism in the worldview of many male Hupu users. Political commentary underscores the rise of nationalism and anti-Western-liberal sentiments in Chinese society. Abstract: As the first edition of the Olympics including transgender sportswomen, Tokyo 2020 brought trans-rights debates to the forefront of global sports spectatorship during the summer of 2021. In this article, we adopt a dialectical-relational approach to address how anti-trans sentiments unfold in male Chinese sports fans' social-mediated communication. Based on textual analysis of posts retrieved from Hupu, the research reveals that anti-trans sentiments are largely informed by an essentialist notion of sex, which considers it to be a purely biological construct that is paramount in policymaking, being perpetuated in the process of China's modernisation. Anti-trans discourses manifest in the sampled postings tend to converge with China's official nationalist rhetoric, projecting critical voices against liberal-progressive values and Western-style democracy. The research findings shed new light on the dialectical relations between nationalist politics and anti-trans sentiments and, by extension, queerphobic views in China's sports fandom, pointing towards the heteronormative monopoly of public discourses in sport and beyond.